Cladosporium cladosporioides 포자에 대한 나노입자의 항진균 특성 평가 - 윤선화; 배귀남; 이병욱; 지준호; 김선정 (한국대기환경학회, 2009)
The antifungal activity of silver, copper, and titania nanoparticles against fungal spores was investigated. Cladosporium cladosporioides spores were aerosolized and sampled on a solid agar plate using an Anderson impactor. The solid agar plate contained different concentration of nanoparticles ranging from 0 to 500 μg/mL. Silver and copper nanoparticles were shown to be an effective antifungal agent, while titania nanoparticles were not. Antifungal activity of these effective nanoparticles appeared at 300 μg/mL concentration.